Experimental investigations on the seismic behavior of composite steel concrete coupled shear walls with central openings. (October 2021) - Todea, V.; Dan, D.; Florut, S.C.; Stoian, V.
Graphical abstract: Highlights: Composite steel–concrete shear walls with central openings and conventionally reinforced coupling beams subjected to cyclic lateral loads were experimentally investigated. Structural steel profiles embedded on the reinforced concrete walls edges could suppress the severe concrete cracking of the tensioned wall, increase the axial stiffness and enhance the bearing capacity and lateral stiffness of the coupled shear walls, when high degree of coupling is generated by stiff coupling beams. Steel fibers supplementary embedded in concrete matrix of composite steel concrete shear wall improved the ductility loss of the walls, due to large openings generated in the solid walls. Perforated steel plates used as shear connectors behaved well under cyclic lateral loads and could be a viable and efficient solution instead of nelson studs, in structural detailing to provide composite action between steel and concrete. Abstract: This paper presents the results of an experimental study performed on concrete structural walls subjected to vertical and cyclic lateral loads. The purpose of the study is to experimentally investigate the seismic behavior and performance of composite steel–concrete coupled walls with regular openings and conventional reinforced coupling beams. The paper also addresses the manner in which the use of steel fibers reinforced concrete and various composite steel–concrete connections influence the hysteretic performance of the walls. Four of the total five experimental specimens had centrally aligned openings, while the fifth one was designed as a solid wall and served as reference. The experimental specimens present various cross-sectional arrangements, thus the testing matrix comprises of a total of three composite steel–concrete walls with central openings (CSRCW) with steel profiles partially embedded on the edges, one conventional reinforced concrete wall (RCW) with central openings and the solid specimen, which is also a composite steel–concrete wall. Based on the experimental results, it was observed that by embedding supplementary steel fibers in the concrete matrix, the ductility loss due to openings could be regained and significantly improved. The composite connection between structural steel and concrete web panel of the walls could successfully resist until the specimens reached the ultimate failure. The paper therefore concludes on the performance of various structural solutions and details by highlighting strengths and weaknesses of the systems.